Origin of spin-polarized photocurrents in the topological surface states of Bi2Se3 - Ketterl, A. S.; Otto, Sebastian; Bastian, M.; Andres, B.; Gahl, C.; Minar, J.; Ebert, H.; Braun, J.; Tereshchenko, O. E.; Kokh, K. A.; Fauster, Thomas; Weinelt, M. (Physical Review B, 2018)
For the generation of spin-polarized photocurrents in topological insulators, a coupling between photon angular momentum and electron spin is often assumed. Such a coupling seems to be supported by dichroism reported in E(k(y))-intensity maps in photoemission. We show in three dimensional two-photon photoemission and one-step photoemission calculations that the circular dichroism is in fact threefold in E(k(x), k(y)) maps although it may appear antisymmetric in E(k(y)). The threefold symmetry is inconsistent with the previously assumed coupling between photon momentum and electron's chiral spin via the orbital momentum. Instead it reflects the surface point group. The only antisymmetric patterns appear in the energy range in which surface and bulk states hybridize. In general, a threefold-symmetric dichroic signal does not support unidirectional photocurrents. Nevertheless, the residual asymmetry of up to 3.5% in our photoemission spectra is compatible with previously observed helicity-dependent photocurrents.